Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/0193723520919819
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Markers of Risky Daily Fantasy Sports Play

Abstract: To understand the natural groups of daily fantasy sports (DFS) players and their associated problematic play, we obtained DFS participation records for 11,130 DFS players from a leading provider. A cluster analysis suggested four player clusters. Cluster 4 included a single highly successful player (i.e., an outlier). Players in Cluster 1 had shorter playing durations than players in Clusters 2 and 3 and picked riskier contests than players in Cluster 3. Players in Cluster 2 picked riskier contests than player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…We assessed whether the centile plot for the distribution of total overall spend would show a clear majority of players with smaller values and a remaining minority with larger values. This study’s distribution of total overall spend has the same right-skewed shape as other distributions related to spending on gambling or similar activities (e.g., Deng et al, 2021 ; Tom et al, 2014 ; Wiley et al, 2020 ). Still, confirming this expectation—that we could separate the cohort into a majority and a minority—was a prerequisite for the comparisons that followed.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We assessed whether the centile plot for the distribution of total overall spend would show a clear majority of players with smaller values and a remaining minority with larger values. This study’s distribution of total overall spend has the same right-skewed shape as other distributions related to spending on gambling or similar activities (e.g., Deng et al, 2021 ; Tom et al, 2014 ; Wiley et al, 2020 ). Still, confirming this expectation—that we could separate the cohort into a majority and a minority—was a prerequisite for the comparisons that followed.…”
Section: Discussionsupporting
confidence: 54%
“…For example, in a scatterplot of win rate per 100 hands versus number of hands played for a group of cash game no limit hold'em players, Siler ( 2010 ) presented a tapered, cone-shaped data cloud where it was not clear that a measure of a linear or even monotonic relationship (e.g., a Pearson or Spearman correlation) was appropriate. In another example, a recent study of new players in another game of skill, daily fantasy sports, Wiley et al ( 2020 ) observed that percent lost and net loss were not significantly correlated. Poker strategy arguments also question the value of assuming simple relationships between measures of poker activity or between measures of gambling activity in general.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 68% of online-based self-excluders were problem gamblers according to the Lie–Bet Questionnaire for internet gambling, and the most common reason gamblers reported for self-exclusion was financial hardship (Motka et al, 2018). DFS player record research suggests that there are distinct markers of players who might be at risk for engaging in risky or harmful DFS play, including referring a friend to DFS, playing duration, and contest selection (Tom et al, 2020; Wiley et al, 2020). Only one study, to our knowledge, has examined a potential predictor of self-exclusion from DFS; that study found that experiencing a big win was not associated with self-exclusion (Edson et al, 2021).…”
Section: History Of Fantasy Sports and The Rise Of Daily Fantasy Sportsmentioning
confidence: 99%
“…To examine how each definition of big wins classifies DFS players (Hypothesis 1), we noted which players had a big win based on just the Custer $1,000 threshold, which players had a big win based on just the Prize Ratio criterion, which players had a big win based on both criteria, and which players did not have a big win. Based on previous research with actual DFS player data (Wiley et al, 2020), we anticipated that a small percentage (less than 0.1%) of DFS players would experience a big win, diversely defined.…”
Section: Hypotheses and Analytic Planmentioning
confidence: 99%